Synthesis and characterization UV-curable organic-inorganic of flame retarding hybrid coatings - KAYAMAN APOHAN, NİLHAN; KARATAŞ, SEVİM (WILEY, 2006)
UV-curable, organic-inorganic hybrid materials were synthesized via sol-gel reactions for tetraethylorthosilicate, and methacryloxypropyl trimethoxysilane in the presence of the acrylated phenylphosphine oxide resin (APPO) and a bisphenol-A-based epoxy acrylate resin. The sol-gel precursor content in the hybrid coatings was varied from 0 to 30 wt %. The adhesion, flexibility, and hardness of the coatings were characterized. The influences of the amounts of inorganic component incorporated into the coatings were studied. Results from the mechanical measurements show that the properties of hybrid coatings improve with the increase in sol-gel precursor content. In addition, thermal properties of the hybrids were studied by thermogravimetric analysis in air atmosphere. The char yield of pure organic coating was 32% and that of 30 wt % silicate containing hybrid coating was 30% at 500 degrees C in air atmosphere. This result demonstrates the pronounced effect of APPO on the flame retardance of coatings. Gas chromatography/mass spectrometry analyses showed that the initial weight loss obtained in thermogravimetric analysis is due to the degradation products of the photoinitator and the reactive diluent. (c) 2006 Wiley Periodicals, Inc.
Keywords: UV-curable coatings; sol-gel materials; nanocomposite; organic-inorganic hybrids; flame resistance; STRUCTURE-PROPERTY BEHAVIOR; PHOTOPOLYMERIZATION; POLYMERS; EPOXY